Analysis of Factors Affecting Creativity in Economics Learning of Students at SMAN 9 Bogor - Saffa, Ismi Makarimal; Wibowo, Agus; Iranto, Dicky (The Future of Education Journal, 2025)
This study aims to determine the analysis of factors that influence learning creativity in economics learning of students at SMAN 9 Bogor. This study was conducted to determine the dominant factors in economics learning at that school. The study used quantitative methods with a quesdtionnaire as a data collection tool.. The questionnaire data was processed using factor analysis with the help of SPSS 25 software. Of the nine factors studied and analyzed using factor analysis, four dominant factors were formed, namely : (1) Interest and relevance of learning factors, which consist of stimulation variables from the school environment and self motivation, (2) Activeness and participation factors, which consist of situational variables that give rise to and encourage the emergence of many questions as well as bilingualism variables, (3) Independence and parental support factors, which consist of situational variables that present incompleteness and openness, situations that encourage producing something, and parental attention to their child’s interests, (4) Independent problem solving factors, which consists of situational variables that emphasize self initiative to explore, observe, ask, and feel, clarify, record, translate, estimate, test of the results of estimates, and communicate.